Cellulose nanofiber-containing carboxy-modified polyolefin and method for producing the same
The crosslinking of carboxy-modified polyolefin with a polyfunctional curing agent in cellulose nanofiber compositions addresses process complexity and thermal stability issues, enabling effective reinforcement of hydrophobic resins.
Patent Information
- Application Number
- JP2023107079
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-06-29
- Publication Date
- 2025-01-17
AI Technical Summary
Existing resin compositions using cellulose nanofibers face challenges such as complex processes, limited resin types due to acid value and melting point restrictions, and insufficient thermal stability, which hinder the full reinforcing effect of cellulose nanofibers.
A cellulose nanofiber-containing composition is developed by crosslinking carboxy-modified polyolefin with a polyfunctional curing agent, ensuring good dispersibility and thermal stability, allowing for a broader range of acid-modified polyolefins and improved thermal stability.
The crosslinked cellulose nanofibers maintain high dispersibility and reinforcing effect while enhancing thermal stability, suitable for a wider variety of hydrophobic resins.
Smart Images

Figure 2025006346000001 
Figure 2025006346000002 
Figure 2025006346000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a reinforcing material that uses cellulose nanofibers to exert a reinforcing effect on resins, and to a reinforced resin composition. [Background technology]
[0002] Cellulose nanofibers, which are plant fibers finely defibrated to the nano level, are characterized by less thermal deformation than glass fibers, high strength, and a low thermal expansion coefficient. These characteristics make them expected to have a stronger reinforcing effect than glass fibers as a reinforcing material for resins and rubbers. However, because cellulose is hydrophilic, it has a low affinity for highly hydrophobic and less polar resins and rubbers, making it difficult to disperse.
[0003] In response to this, a technology has been reported that improves dispersibility in resins and rubbers by modifying the surface of cellulose nanofibers through the introduction of functional groups. However, the process of introducing functional groups after defibrating the cellulose nanofibers is complicated and requires a large workload.
[0004] Patent Document 1 proposes a resin composition in which a dried product of cellulose nanofibers to which a surfactant has been added is mixed with acid-modified polypropylene or a polyolefin resin, and then melt-kneaded. In this resin composition, cellulose nanofibers obtained in an aqueous dispersion state are highly dispersed in a polyolefin resin, which is a hydrophobic resin, improving the physical properties of the hydrophobic resin.
[0005] Patent Document 2 proposes a composition in which an aqueous suspension of cellulose nanofibers is mixed with an aqueous emulsion of a polyolefin containing a carboxy group, and then an acid is added to precipitate the polyolefin. This composition is characterized by the high dispersibility of the cellulose nanofibers contained therein and the ease of mixing with other hydrophobic resins.
[0006] Furthermore, Patent Document 3 proposes a rubber vulcanizate for rolls that contains modified polyolefin, cellulose nanofibers, and non-polar rubber, in which the modified polyolefin and the non-polar rubber are crosslinked and the cellulose nanofibers are dispersed. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] Patent No. 6889358 [Patent Document 2] Patent No. 6591304 [Patent Document 3] Patent No. 7235257 Summary of the Invention [Problem to be solved by the invention]
[0008] However, in Patent Document 1, a surfactant must be added and spray-dried to prevent the aggregation of cellulose nanofibers, which makes the process complicated and there is a risk that the surfactant may impair the thermal stability of the resin composition.
[0009] In addition, the composition described in Patent Document 2 was required to have an acid value of 50 mg / KOH or less and a melting point of 80° C. or more as an acid-modified polyolefin having a carboxy group. If the acid value is too high, the physical properties of the resulting resin composition are inferior or the resin composition has no water resistance, and if the melting point is too low, the strength of the resulting resin composition is likely to decrease. These conditions limit the types of resins that can use the composition of Patent Document 2 as a reinforcing material, and there is also the problem that the resulting resin composition has low thermal stability.
[0010] Furthermore, the rubber vulcanizate described in Patent Document 3 has insufficient thermal stability, and there is a concern that its applications may be limited.
[0011] Therefore, the object of the present invention is to increase the types of acid-modified polyolefins that can be used for resin compositions that contain cellulose nanofibers and exhibit a reinforcing effect when added to a resin, and to obtain a resin composition in which the reinforcing effect of the cellulose nanofibers is fully exerted. [Means for solving the problem]
[0012] The present invention solves the above-mentioned problems by providing a cellulose nanofiber-containing composition comprising cellulose nanofibers and a crosslinking reaction product in which a carboxy-modified polyolefin is crosslinked with a multifunctional curing agent.
[0013] In other words, by crosslinking a carboxy-modified polyolefin, which has the role of dispersing and holding cellulose nanofibers, with a multifunctional curing agent to form a crosslinking reaction product, it is possible to improve the thermal stability of the carboxy-modified polyolefin itself while maintaining the dispersibility of the cellulose nanofibers in a good state. As a result, a resin composition in which a cellulose nanofiber-containing composition is added to a hydrophobic resin can exhibit a high reinforcing effect due to the cellulose nanofibers introduced in a well-dispersed state while ensuring thermal stability.
[0014] The procedure for producing the cellulose nanofiber-containing composition according to the present invention is to mix an aqueous carboxy-modified polyolefin emulsion, a cellulose nanofiber-containing slurry, and a multifunctional curing agent, and then heat and dry the mixture. The heat generated at this time is used by the multifunctional curing agent to crosslink the carboxy-modified polyolefin, thereby enhancing the thermal stability of the resin containing the cellulose nanofiber-containing composition. At this time, the multifunctional curing agent may react with the hydroxyl groups of the cellulose nanofibers.
[0015] In addition, a method for producing a resin composition from the cellulose nanofiber-containing composition of the present invention includes kneading the cellulose nanofiber-containing composition obtained by the above procedure into a hydrophobic resin. The cellulose nanofibers are suitably dispersed in the resin composition, and the resin composition exhibits improved strength and thermal stability compared to conventional resin compositions. Effect of the Invention
[0016] In the cellulose nanofiber-containing composition of the present invention, the carboxy-modified polyolefin is crosslinked by a multifunctional curing agent, so that the acid value and melting point of the carboxy-modified polyolefin used are not limited as compared to conventional reinforcing materials, and even carboxy-modified polyolefins with low melting points can be treated as having high thermal stability. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0017] The present invention is described in detail below. The present invention relates to a cellulose nanofiber-containing composition, which is used as a resin composition that exhibits a reinforcing effect when added to a hydrophobic resin.
[0018] The cellulose nanofibers (hereinafter abbreviated as "CNF") used in this invention are cellulose materials processed to produce fine fibers. It is preferable that the cellulose is unsubstituted, with no change in the molecular structure of the cellulose. However, it may be that part of the cellulose is once substituted during the production process of CNF to facilitate defibration, and after defibration, the substituents are restored to their original state to regenerate cellulose. Examples of chemically modified cellulose that can be regenerated into cellulose after such substitution include phosphated cellulose and xanthated cellulose, but are not particularly limited to these as long as it is regenerated as cellulose. In the CNF obtained by such regeneration, it is preferable that the remaining amount of the substituents is as small as possible, and it is preferable that all the substituents are regenerated.
[0019] In this way, by using unsubstituted or equivalent CNF, there is less interference with the resin emulsion or polyfunctional curing agent when mixing with the resin emulsion described later, so the dispersibility of the CNF is not impaired. This allows the crosslinking reaction to proceed in a dispersed state of the CNF. In addition, the absence of a substituent in the CNF makes it difficult to thermally decompose because its thermal decomposition temperature is high, making it easy to knead with the hydrophobic resin described later, and it is also preferable in that the kneaded product is less likely to discolor when molded.
[0020] The number average fiber diameter of CNF is preferably 2 nm or more, more preferably 4 nm or more. The present invention can be carried out with a diameter smaller than this, but a diameter smaller than 2 nm requires a large amount of energy and is not very practical in terms of work efficiency. On the other hand, the number average fiber diameter of CNF is preferably 40 nm or less, more preferably 35 nm or less. If it exceeds 40 nm, a dense network cannot be formed in the resin composition, and the intended reinforcing effect may not be fully exerted.
[0021] As an index of the fiber diameter distribution of CNF, for example, the standard deviation of the fiber diameter measured by arbitrarily selecting 50 nanofibers can be used. This standard deviation is preferably 10 nm or less, and more preferably 7 nm or less. If it exceeds 10 nm, the inclusion of CNF with a large fiber diameter cannot be ignored, and the intended reinforcing effect may not be fully exerted.
[0022] The CNF-containing composition of the present invention contains, in addition to CNF, a crosslinking reaction product formed by crosslinking a carboxy-modified polyolefin with a multifunctional curing agent.
[0023] The above-mentioned carboxy-modified polyolefin has a polyolefin skeleton and a carboxy group in part. Although it is possible to use a carboxy group in an acidic -COOH state, if the pH becomes too low, the CNFs tend to aggregate, and it is possible that a resin composition in which the CNFs are uniformly dispersed cannot be obtained. Therefore, it is preferable to use a basic -COO - M +(M is an alkali metal) is preferred.
[0024] The acid value indicating the degree of modification of this carboxy-modified polyolefin is preferably 1 mgKOH / g or more, more preferably 20 mgKOH / g or more. If it is less than 1 mgKOH / g, the amount of carboxy groups is too small, so crosslinking does not proceed sufficiently, and the effect of improving thermal stability tends to be insufficient. On the other hand, it is preferably 80 mgKOH / g or less, more preferably 70 mgKOH / g or less. If there are too many carboxy groups, the molecular weight of the polyolefin itself during carboxy modification is reduced, and there is a risk that sufficient strength of the resin composition cannot be obtained even if crosslinked with a multifunctional curing agent.
[0025] The pH of the emulsion of the above carboxy-modified polyolefin before crosslinking is preferably 4 or more, more preferably 8 or more. If it is strongly acidic (less than 4), it is prone to deterioration at high temperatures, which is problematic in terms of thermal stability. If it is weakly basic (8 or more), it is prone to crosslinking reaction and is less prone to deterioration at high temperatures than when it is acidic. On the other hand, even if it is strongly basic, CNFs tend to aggregate, which may prevent the production of a resin composition in which CNFs are uniformly dispersed, so the pH is preferably 11 or less.
[0026] The polyfunctional curing agent has a plurality of functional groups that react with carboxy groups and acts as a crosslinking agent for the carboxy-modified polyolefin. There are no limitations on the type of the curing agent as long as it can react with a carboxy group, and examples of the crosslinking agent include polyisocyanate-based crosslinking agents and epoxy-based crosslinking agents.
[0027] The equivalent ratio of the carboxy group of the carboxy-modified polyolefin to the functional group of the multifunctional curing agent is preferably 100:1 to 1:2. If the amount of the multifunctional curing agent is too much relative to the amount of the carboxy-modified polyolefin, crosslinking may proceed too much, resulting in poor thermoplasticity and making it impossible to knead the resin. On the other hand, if the amount of the multifunctional curing agent is too little, crosslinking may be insufficient, resulting in insufficient effect of improving thermal stability.
[0028] In producing a CNF-containing composition having a crosslinked reaction product in which these carboxy-modified polyolefins and polyfunctional curing agents are crosslinked, and CNF, for example, the following procedure can be suitably used. However, as long as a similar reaction is possible, the procedure is not particularly limited to this. First, a CNF water slurry is prepared by dispersing CNF in water. This may be a slurry obtained when cellulose is defibrated or regenerated into CNF, and the content may be adjusted to an appropriate level. Next, a resin emulsion in which a carboxy-modified polyolefin is dispersed in water is added to this CNF water slurry. After adding the resin emulsion, a polyfunctional curing agent is added, and the mixture is heated and dried to reduce the water contained in the resin emulsion and the CNF water slurry, and the crosslinking reaction is promoted to obtain a CNF-containing composition.
[0029] In this CNF-containing composition, the mass mixing ratio of CNF to the crosslinking reactant is preferably 1:20 to 1:1. If the amount of CNF is too much, the CNF-containing composition becomes too hard, and the dispersion of CNF becomes insufficient when kneaded with other resins. On the other hand, if the amount of crosslinking reactant is too much, the content of carboxy-modified polyolefin becomes high, which may impair the physical properties of other resins kneaded with the crosslinking reactant.
[0030] By adding the CNF-containing composition thus obtained to a hydrophobic resin such as rubber and kneading it, the CNF that was kept in a well-dispersed state is uniformly dispersed in the hydrophobic resin, thereby obtaining a resin composition in which the reinforcing effect of the CNF is optimally exerted.
[0031] Examples of the hydrophobic resin include polyolefin resins, hydrocarbon synthetic rubbers, polyester resins, and polyamide resins. Among these, resins with the smallest possible polarity can enjoy the maximum benefit of reinforcing with the CNF-containing composition of the present invention. Although it can also be used for resins with high polarity such as acrylic resins, highly polar resins have a high affinity with hydrophilic cellulose, and a resin composition in which CNF is sufficiently dispersed can be obtained without using the CNF-containing composition of the present invention, so there is little benefit to using the present invention.
[0032] Examples of the polyolefin resins include polyethylene, polypropylene, polycyclodecane, polycyclopentadiene, and polymethylterpene. Examples of the hydrocarbon synthetic rubbers include ethylene propylene rubber (EPDM) and styrene butadiene rubber. Examples of the polyester resins include polyethylene terephthalate, polybutylene terephthalate, polylactic acid, and polycaprolactone. Examples of the polyamide resins include nylon 6, nylon 66, nylon 11, and nylon 12.
[0033] When the CNF contained in the CNF-containing composition is mixed with the hydrophobic resin in a mass ratio of 100:1 to 4:1, the hydrophobic resin can be suitably reinforced. If the amount of CNF is too small, the reinforcing effect is not sufficiently exhibited, and if the amount of CNF is too large, unexpected effects other than strength may occur.
[0034] The resin composition thus obtained exhibits a favorable reinforcing effect on the original hydrophobic resin and exhibits a high storage modulus. EXAMPLES
[0035] Examples of specific implementations of the present invention are described below. First, the materials used are described. The fiber diameter standard deviation was measured by randomly selecting 50 nanofibers from an image of 50,000 times magnification observed using a transmission electron microscope (TEM: JEM-1400, manufactured by JEOL Ltd.) and measuring the standard deviation of the fiber diameters. CNF (water slurry): Rengo Co., Ltd.: RCNF, number average fiber diameter 5.9 nm, fiber diameter standard deviation 1.0 nm, solid content 1.4 mass%, unsubstituted cellulose regenerated from cellulose xanthate. Mechanically defibrated CNF (water slurry): Sugino Machine Co., Ltd.: BiNFi-S: Product number WFo10005: number average fiber diameter 31 nm, fiber diameter standard deviation 7.3 nm, solid content 5.0 mass%. TEMPO-oxidized CNF: Prepared according to the example in Patent No. 6668558: Number average fiber diameter 6.3 nm: Standard deviation of fiber diameter 1.1 nm: Average degree of oxidation 2 mmol / g). CNF substituted with carboxyl groups. <Carboxy-modified polyolefin: both manufactured by Unitika Ltd., aqueous dispersion> DA-1010: Melting point 75℃, acid value 35mgKOH / g, pH 9, polypropylene SB-1010: Melting point 80℃, acid value 25mgKOH / g, pH 9, polyethylene DC-1010: Melting point 140℃, acid value 55mgKOH / g, pH 9, polypropylene <Multifunctional curing agent> Isocyanate-based crosslinking agent: Asahi Kasei Corporation: Duranate WB40-100, "Isocyanate" in the table Epoxy-based crosslinking agent: ADEKA Corporation: ADEKA Resin EM-101-50, "Epoxy" in the table <Hydrophobic resin> Ethylene propylene rubber (EPDM): ENEOS Materials Co., Ltd.: EP T7241 Low-density polyethylene (LDPE): Tosoh Corporation: Petrothene 205, melting point 111°C <Vulcanization aid> Zinc oxide: Nacalai Tesque, Inc. (reagent grade 1) <Vulcanizing agent> · Dicumyl peroxide (DCP): Manufactured by Nacalai Tesque, Inc.: Chemical reagent
[0036] <Preparation of CNF-containing composition> (Example 1) First, a CNF aqueous slurry, which is a slurry in which CNF is dispersed in water, is diluted with water to prepare 1,000 g of a diluted solution (CNF content: 10 g) with a solid content of 1.0% by mass. While stirring this at 3,000 rpm with a homodisper (Lab Revolution manufactured by Primix Corporation), 92 g (solid content: 23 g) of SB-1010, which is a resin emulsion in which carboxy-modified polyolefin is dispersed in water, is added. Subsequently, 2.6 g of WB-40-100, which is a polyfunctional curing agent (equivalent ratio of functional groups to carboxy groups: 0.25), is added and stirred for 5 minutes. This is dried by blowing air at 60°C for 24 hours to advance the cross-linking reaction of the carboxy-modified polyolefin with the polyfunctional curing agent, thereby obtaining a CNF-containing composition (CNF content: 10 g, solid content: 35.6 g).
[0037] <Manufacture of resin composition with EPDM> To the CNF-containing composition (CNF 10 g, solid content 35.6 g) obtained above, 100 g of EPDM, which is a hydrophobic resin, 3 g of DCP, which is a vulcanizing agent, and 5 g of zinc oxide, which is a vulcanization aid, are added, and kneaded at 80°C with an open roll (Test Mixing Roll manufactured by Yasuda Seiki Seisakusho Co., Ltd.) to obtain a resin composition in which CNF is dispersed. This resin composition is compression-molded at 170°C × 20 MPa for 15 minutes to obtain a rubber sheet. For this rubber sheet, the storage elastic modulus is measured at 25°C and 100°C environments with an initial test force of 0.1 N, a strain of 2%, a frequency of 7 Hz, and a heating rate of 3°C / min using DMA850 manufactured by TA Instruments. Also, a dumbbell-shaped No. 3 test piece specified in JIS K6251 is punched out from this rubber sheet, and a tensile test (grip width: 50 mm, tensile speed: 500 mm / min) is performed using a tensile tester (Autograph AGS-X manufactured by Shimadzu Corporation) according to JIS K6252. The composition ratio and measurement results are shown in Table 1. In Table 1, "phr" is the mass ratio with EPDM as 100.
[0038] [Table 1]
[0039] (Comparative Example 1: No CNF, multifunctional curing agent, or carboxy-modified polyolefin) A rubber sheet was obtained in the same manner as in Example 1, except that the CNF-containing composition was not added and only EPDM, DCP, and zinc oxide were kneaded. The composition ratio and measurement results are shown in Table 1.
[0040] (Comparative Example 2: No CNF & multifunctional curing agent) A rubber sheet was obtained in the same manner as in Example 1, except that the CNF water slurry in Example 1 was replaced with the same mass of water containing no CNF, and no multifunctional curing agent was added. That is, compared to Example 1, the CNF and multifunctional curing agent were removed, and the carboxy-modified polyolefin remained. The composition ratio and measurement results are shown in Table 1.
[0041] (Comparative Example 3: No multifunctional curing agent) A rubber sheet was obtained in the same manner as in Example 1, except that no polyfunctional curing agent was added. The composition ratio and measurement results are shown in Table 1.
[0042] (Comparative Example 4: No CNF) A rubber sheet was obtained in the same manner as in Example 1, except that the CNF water slurry was replaced with the same mass of water not containing CNF. The composition ratio and measurement results are shown in Table 1.
[0043] (Consideration) Compared to Comparative Example 1, the storage modulus was improved even for the rubber sheets containing only carboxy-modified polyolefin (Comparative Example 2), carboxy-modified polyolefin and CNF (Comparative Example 3), and carboxy-modified polyolefin and a multifunctional curing agent (Comparative Example 4). However, Example 1, which contains all of them, showed a clear improvement in storage modulus compared to those comparative examples, and it was confirmed that the effect of the present invention was exerted. In particular, when comparing Example 1 with Comparative Example 3, which does not have a multifunctional curing agent, Example 1, in which the carboxy-modified polyolefin is crosslinked, showed a higher storage modulus, despite also having CNF and carboxy-modified polyolefin. This is presumed to be because the CNF is mixed into the hydrophobic resin in a more suitably dispersed state by crosslinking the carboxy-modified polyolefin, improving the reinforcing effect. In addition, from the comparison between Comparative Example 2 and Comparative Example 4, it is presumed that the added multifunctional curing agent does not particularly contribute to the reinforcement of the hydrophobic resin, but is mainly used for crosslinking the carboxy-modified polyolefin.
[0044] (Examples 2 and 3) A CNF-containing composition was obtained and a rubber sheet was obtained in the same manner as in Example 1, except that the amount of the multifunctional curing agent was doubled and quadrupled. The composition ratio and measurement results are shown in Table 1. The storage modulus was further improved compared to Example 1, and it was confirmed that even with the same amount of CNF, the reinforcing effect of CNF was improved due to the progress of crosslinking of the carboxy-modified polyolefin.
[0045] (Comparative Examples 5 and 6) In Examples 2 and 3, rubber sheets were obtained in the same manner as in Examples 2 and 3, except that the CNF water slurry was replaced with the same mass of water that did not contain CNF. The composition ratios and measurement results are shown in Table 1. Examples 2 and 3 showed a large improvement in storage modulus compared to Example 1, but Comparative Examples 5 and 6, which had no CNF and only an increased amount of multifunctional curing agent, showed a small increase in storage modulus at 100°C compared to Comparative Example 4. For this reason, it is believed that the increase in multifunctional curing agent is not simply a reinforcement due to the addition of resin, but contributes to a reinforcing effect that occurs by acting on the CNF.
[0046] <Change in the type of polyfunctional curing agent> (Examples 4 and 5) In Example 1, the polyfunctional curing agent used was changed from WB-40-100 (isocyanate) to EM-101-50 (epoxy), and the equivalent ratio of the functional group to the carboxy group was changed to 0.05 (Example 4) and 0.2 (Example 5). A rubber sheet was obtained by the same procedure as in Example 1 except for this change. The composition ratio and measurement results are shown in Table 1. It was confirmed that even when the type of polyfunctional curing agent was different, the reinforcing effect of the hydrophobic resin and the thermal stability were improved.
[0047] (Comparative Examples 7 and 8) In Examples 4 and 5, a rubber sheet was obtained by the same procedure as in Examples 4 and 5, respectively, except that the CNF aqueous slurry was changed to the same mass of water not containing CNF. The composition ratio and measurement results are shown in Table 1. Compared with Examples 4 and 5, in Comparative Examples 7 and 8 in which only the polyfunctional curing agent was added without CNF, no improvement in the storage elastic modulus at 100 °C was particularly observed.
[0048] <Change in the type of carboxy-modified polyolefin> (Examples 6 and 7) In Example 1, a rubber sheet was obtained by the same procedure as in Example 1 except that the carboxy-modified polyolefin used was changed to DA-1010 (Example 6) and DC-1010 (Example 7). The composition ratio and measurement results are shown in Table 1. It was confirmed that even when the type of carboxy-modified polyolefin was different, the reinforcing effect of the hydrophobic resin and the thermal stability were improved.
[0049] (Comparative Examples 9 and 10) In Examples 6 and 7, a rubber sheet was obtained by the same procedure as in Examples 6 and 7, respectively, except that no polyfunctional curing agent was added. The composition ratio and measurement results are shown in Table 1. Compared with Examples 6 and 7, in Comparative Examples 9 and 10 having no polyfunctional curing agent, the storage elastic modulus at 100 °C particularly decreased.
[0050] <Change in the type of CNF> (Example 8) In Example 4, a rubber sheet was obtained in the same procedure as in Example 4 except that the CNF used was changed to mechanically fibrillated CNF. The composition ratio and measurement results are shown in Table 1. When the type of CNF was changed, although not as much as in Example 4, it was confirmed that the reinforcing effect of the hydrophobic resin and the thermal stability were improved.
[0051] (Comparative Example 11) In Example 8, a rubber sheet was obtained in the same procedure as in Example 8 except that the polyfunctional curing agent was not added. The composition ratio and measurement results are shown in Table 1. Compared with Example 8, in Comparative Example 11, the storage modulus at 100 °C particularly decreased.
[0052] (Preparation of Resin Composition with LDPE) (Example 9) To 3.1 g of the CNF-containing composition obtained in Example 4 (10 g of CNF, 35.6 g of solid content), 9.4 g of LDPE, a hydrophobic resin, was added, and using a desktop small kneader (manufactured by Xplore Instruments: DSM Xplore MC15M), it was kneaded at 140 °C for 5 minutes and injection molded into strip shape to obtain a test piece (length 80 mm × width 10 mm × thickness 2 mm) of the resin composition in which CNF was dispersed. This test piece was cut into a length of 40 mm, and a three-point bending test (test speed: 0.1 mm / min, distance between supports: 20 mm) was performed using a dynamic mechanical analyzer (manufactured by TA Instruments, DMA850), and the flexural modulus was calculated from the stress gradient of the obtained bending strain of 0.05% to 0.25%. Also, using the same apparatus, a load deflection temperature measurement (load: 0.45 MPa, heating rate: 2 °C / min) was performed, and the temperature at which the bending deflection became 1% of the obtained result was defined as the load deflection temperature. The composition ratio and measurement results are shown in Table 2. In Table 2, "phr" is the mass ratio with LDPE as 100.
[0053]
Table 2
[0054] (Example 10) A resin composition having CNF dispersed therein was obtained in the same manner as in Example 9, except that the amount of the multifunctional curing agent was four times that of Example 9. The composition ratio and the measurement results are shown in Table 2.
[0055] Comparative Example 13 A resin composition was obtained in the same manner as in Example 9, except that the CNF-containing composition was not used and only LDPE was used. The composition ratio and measurement results are shown in Table 2.
[0056] (Comparative Examples 14 and 15) Resin compositions were obtained in the same manner as in Example 9, except that in Example 9, the polyfunctional curing agent was not added, the CNF water slurry was changed to water not containing CNF (Comparative Example 14), and no polyfunctional curing agent was added (Comparative Example 15). The composition ratios and measurement results are shown in Table 2.
[0057] (Consideration) The LDPE (Examples 9 and 10) kneaded with the CNF-containing composition crosslinked with the carboxy-modified polyolefin had improved flexural modulus and increased deflection temperature under load compared to Comparative Example 13, which contained only LDPE. In Comparative Example 14, which contained only the carboxy-modified polyolefin, the flexural modulus and deflection temperature under load were lower than those of Comparative Example 13, possibly because the LDPE was diluted with the carboxy-modified polyolefin. Furthermore, in Comparative Example 15, which did not contain a multifunctional curing agent, the flexural modulus and deflection temperature under load were lower than those of Example 9. This shows that the addition of the CNF-containing composition crosslinked with the carboxy-modified polyolefin makes it possible to achieve both the reinforcing effect of the CNF and the improvement of thermal stability.
[0058] <Confirmation of physical properties of carboxy-modified polyolefin used> The carboxy-modified polyolefin used above has a carboxy group in the acid form of -COOH, not -COO - M +To confirm that it is in the basic form, the ash content was measured according to JIS K7250. First, for DA-1010 and DC-1010 which are carboxy-modified polyolefins, the mass before and after ashing was measured for the solid content obtained by drying them, and the residual rate of ash was measured (Reference Examples 1 and 2). The results are shown in Table 3 below. Also, after adding an acid to the emulsions of DA-1010 and DC-1010 to adjust the pH to 3, the mass before and after ashing was measured for the solid content obtained by filtration, and the residual rate of ash was measured (Reference Examples 3 and 4). The results are also shown in Table 3 below. Ash remained before adjustment, but almost no ash remained after acid adjustment. Therefore, it was confirmed that the carboxy-modified polyolefin before adjustment exists in the state of the Na salt which is an alkali metal with residual ash.
[0059]
Table 3
[0060] Also, when the Na content in the ash was measured by scanning electron microscope - energy dispersive X-ray spectroscopy (SEM-EDS, manufactured by JEOL Ltd., JSM-6010PLAS / L), the Na content in the carboxy-modified polyolefin before pH adjustment was around 30% by mass, whereas it was around 2% by mass after adjustment. Before pH adjustment, the carboxy group was -COO - Na + was considered to be in the basic form, which was supported by the above.
[0061] <Confirmation of the form of CNF> (Comparative Example 16) In Example 9, TEMPO-oxidized CNF with carboxy group substitution was used instead of CNF, and a resin composition in which TEMPO-oxidized CNF was dispersed was prepared by the same procedure as in Example 1 except for this.
[0062] The resin composition of Example 9 and the resin compositions of Comparative Examples 13 and 16 were hot-pressed for 5 minutes in an environment of 120°C and 3 MPa to prepare a film, and then held for 20 minutes in an environment of 180°C and 1 MPa, which is assumed to be kneaded with a hydrophobic resin. The yellowness index (YI) of the film after heating was measured using a spectrophotometer (CM-3600A, manufactured by Konica Minolta, Inc.) according to JIS K7373. The results are shown in Table 4 below. It was confirmed that the yellowness index was low in Example 9, whereas the yellowness index was high in Comparative Example 16, which used TEMPO-oxidized CNF having a carboxy group. From this, it was confirmed that TEMPO-oxidized CNF having a carboxy group is easily discolored by heat, and CNF having no substituent is preferable.
[0063] [Table 4]
Claims
1. a crosslinking reaction product obtained by crosslinking a carboxy-modified polyolefin with a multifunctional curing agent; A cellulose nanofiber-containing composition comprising cellulose nanofibers.
2. a crosslinking reaction product obtained by crosslinking a carboxy-modified polyolefin with a multifunctional curing agent; Cellulose nanofibers, A resin composition comprising:
3. A method for producing a cellulose nanofiber-containing composition, comprising mixing an aqueous carboxy-modified polyolefin, a cellulose nanofiber-containing slurry, and a multifunctional curing agent, and drying the mixture.
4. A water-based carboxy-modified polyolefin, a cellulose nanofiber-containing slurry, and a multifunctional curing agent are mixed and dried to prepare a cellulose nanofiber-containing composition; A method for producing a resin composition, comprising adding the cellulose nanofiber-containing composition to a hydrophobic resin and kneading the resin to disperse the cellulose nanofibers.
5. A method for producing a resin composition, comprising adding the cellulose nanofiber-containing composition according to claim 1 to a hydrophobic resin and kneading the resin to disperse the cellulose nanofibers.
Citation Information
Patent Citations
Easily dispersible cellulose composition, method for producing easily dispersible cellulose composition, cellulose-dispersed resin composition, and method for producing cellulose-dispersed resin composition
JP6591304B2
Cellulose nanofiber-containing resin composition
JP6889358B2
Rubber vulcanizate for rolls and its manufacturing method
JP7235257B2